Comparative Analysis of Clientelistic Democracy in India and Indonesia: Outcomes and Challenges - Jati, Wasisto Raharjo (Political Science Program, Universitas Negeri Semarang, 2022)
This articles aims at analysing the clientelistic democracy between India and Indonesia. Two countries are considerably the leading democtatic countries in the world. However, recently it seems both countries face declining democracy. One main thing that drives democracy to decline is clientelism. This practice has various intepretations in many practiical ways. This article uses qualitative method, particularly critical literature review. Some relevant literatures that derive from journal and books will be the main source. The findings of this study are while the clintelism practice in India is incorporate in party system, Indonesian version of clientelism does not follow in institutionalisation. Instead, the perpretrators behind the clientelist practice are the informal actors, who famously known as tim sukses “success team”. In a nutshell, democracy seems run well in procdural way, but it has delined gradually due to clientlistic practices.